The globalization of sexuality - Binnie, Jon (SAGE, 2004)
`Lively and engaging... the themes of the chapters are well chosen and cover areas in which several key debates have taken place' - Nina Wakeford, University of Surrey What are the relations between homosexuality, globalization and social theory? Why has the debate on globalization paid so little attention to questions of sexuality? This timely and stimulating book explores the relationships between the national state, globalization and sexual dissidence. The book focuses on several key test issues to exploit and develop analysis: